2019
DOI: 10.1186/s12931-019-1173-0
|View full text |Cite
|
Sign up to set email alerts
|

High level of fluorescent oxidation products and worsening of asthma control over time

Abstract: High Fluorescent oxidation products level (FlOPs), a global oxidative stress biomarker, was associated cross-sectionally with poor asthma outcomes but its longitudinal association with asthma evolution has never been examined. We aimed to study the associations between FlOPs level at baseline and changes in current asthma, asthma attacks and asthma control status over 8 years. We used data from the second survey of the French EGEA cohort study as baseline and the third survey as follow-up. At baseline, the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The results of this study would establish whether ETBF could adversely influence asthma in people and define the environmental and microbial circumstances that enable ETBF to cause these phenotypes. Additionally, the outcomes of such a clinical study could also link two previously disparate features of asthma: first, that increased gut permeability (68, 69) and increased gastrointestinal symptoms (70) have been observed in patients with asthma, and secondly, that increased oxidative stress is associated with more severe asthma with a higher rate of exacerbations and corticosteroid resistance (2, 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study would establish whether ETBF could adversely influence asthma in people and define the environmental and microbial circumstances that enable ETBF to cause these phenotypes. Additionally, the outcomes of such a clinical study could also link two previously disparate features of asthma: first, that increased gut permeability (68, 69) and increased gastrointestinal symptoms (70) have been observed in patients with asthma, and secondly, that increased oxidative stress is associated with more severe asthma with a higher rate of exacerbations and corticosteroid resistance (2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…While asthma is predominately associated with T helper (Th)-2 inflammation associated with high levels of cytokines IL-4, IL-5, and IL-13, detailed characterization from clinical studies has revealed substantial heterogeneity in immunopathology of this disease (1). For example, signs of Th17-associated inflammation and oxidative stress are associated with corticosteroid resistance and increased frequency of exacerbations (2) (2, 3) (4). Although disease heterogeneity plays an important role in the prognosis and treatment of asthma, the factors that drive the phenotype of asthma are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the outcomes of such a clinical study could also link two previously disparate features of asthma: first, that increased gut permeability 69 , 70 and increased gastrointestinal symptoms 71 have been observed in patients with asthma, and secondly, that increased oxidative stress is associated with more severe asthma with a higher rate of exacerbations and corticosteroid resistance. 72 , 73 …”
Section: Discussionmentioning
confidence: 99%
“…The FlOPs level was found to be associated with chronic diseases such as coronary heart disease (CHD) (e.g., incidence of CHD among men without previous cardiovascular events, and risk of future CHD in healthy women) [7,8], and chronic kidney diseases [9]. Recently, we reported that high FlOPs level was associated with asthma attacks, the use of any asthma treatment, and poor control of asthma and was a predictor of asthma evolution in adults from the French Epidemiological study on the Genetics and Environment of Asthma (EGEA) [10,11]. We also found that smoking increased the FlOPs level [11].…”
Section: Introductionmentioning
confidence: 99%